India Vs China in the Agricultural Sector - An Empirical Study - Sam Luther, C. T. (Prabandhan: Indian Journal of Management, 2010)
India and China are the two most talked about Asian countries in recent times in terms of economic growth, but both have resorted to different routes for their growth. Both the countries are growing rapidly and virtually today, they are the key drivers of the world economy. They are competing with each other at one level; at the same time, they are cooperating with each other through joint ventures to maximise trade opportunities. There was a time, when the world looked to the West with wonder, but not anymore. Now, the East is beginning to appear a lot more interesting, because of the emerging economic growth of India and China and their ramifications on the global economic scene. Despite their massive populations and the problems associated thereto, they are quite different in their economic structures, sources of growth, and areas of competitive advantage. And the impact they make, will remain different in the coming years.